Economic Value Analysis and Waste Burden of Household Unused Medicines in Four Districts of Garut Regency - Serli Silviani; Raden Aldizal Mahendra Rizkio Syamsudin; Risrina Nur Ekawati (Fundamental and Applied Research in Medicine and Allied Sciences Indonesia, 2025)
Medicines are substances or products including biological products, that play an important role in prevention, treatment, rehabilitation, and health promotion. Leftover medicines are unused medicines resulting from discontinued treatment or expired dates. Purpose: This study aims to analyze the burden of household medicine waste and its economic losses in Garut Regency. Method: the study employs a quantitative survey method with a cross-sectional design, using quota sampling for sample selection, along with specific inclusion and exclusion criteria. Data were collected through a ReDiUM validated questionnaire. The analysis was conducted using descriptive quantitative methods. Result: the results showed that the economic value of unused drugs amounted to Rp6,410,500 or an average of Rp16,026/ household, with a total household pharmaceutical waste burden of 2.6 kg. Drug classification was dominated by prescription drug at 48%. Implications: these findings indicate that improper management of drug waste can result in economic losses and health and environmental risks. Conclusion: Economic loss and environmental risk could be possibly emerged in the nearest future caused by this losses.